2013
DOI: 10.1038/nchem.1617
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic control over supramolecular gel formation

Abstract: Low-molecular-weight gels show great potential for application in fields ranging from the petrochemical industry to healthcare and tissue engineering. These supramolecular gels are often metastable materials, which implies that their properties are, at least partially, kinetically controlled. Here we show how the mechanical properties and structure of these materials can be controlled directly by catalytic action. We show how in situ catalysis of the formation of gelator molecules can be used to accelerate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
226
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 257 publications
(238 citation statements)
references
References 43 publications
5
226
1
Order By: Relevance
“…As such, catalysis is used as a form of kinetic control over supramolecular structure formation. 45 At the origin of these differences in macroscopic properties lies a change in the morphology of the network that depends on the rate of network formation. Using microscopy techniques such as confocal laser scanning fluorescence microscopy (CLSM) or scanning electron microscopy (SEM), we observed dense, well connected networks when a catalyst was used during formation, whereas uncatalyzed gels consisted of a much less dense, poorly connected network of bundled fibers ( Figure 5).…”
Section: Kinetic Controlmentioning
confidence: 99%
“…As such, catalysis is used as a form of kinetic control over supramolecular structure formation. 45 At the origin of these differences in macroscopic properties lies a change in the morphology of the network that depends on the rate of network formation. Using microscopy techniques such as confocal laser scanning fluorescence microscopy (CLSM) or scanning electron microscopy (SEM), we observed dense, well connected networks when a catalyst was used during formation, whereas uncatalyzed gels consisted of a much less dense, poorly connected network of bundled fibers ( Figure 5).…”
Section: Kinetic Controlmentioning
confidence: 99%
“…The first example of the use of an alkaline phosphatase to trigger the formation of a hydrogel by the dephosphorylation of 9-fluorenylmethoxycarbonyl (Fmoc)-tyrosine phosphate [18][19][20] preceded several others. [21][22] Hirst et al have shown that the amount of biocatalyst used can direct the self-assembly pathway resulting in (kinetic) control of the supramolecular organization of the final supramolecular structure. 23 They also demonstrated that these kinetically locked gels may be ÔunlockedÕ to access a minimum energy state by performing a heat/cool cycle.…”
Section: -2mentioning
confidence: 99%
“…Now, we wish to exploit the full power of chemical synthesis to construct CRNs tuned by small molecules approaching the tunability and functionality of living systems. Although impressive progress in this direction has been made [20][21][22][23][24][25] , we lack a general methodology based on rational design that integrates the structure of (small) molecules with the tuning of the reaction rates for each step in the network. We require a modular approach using common building blocks and reaction conditions, and the ability to program a functional output of the network.…”
mentioning
confidence: 99%